Implementation of cardiology tele-visits after COVID-19 pandemic: the INFO-COVID survey. (14th October 2021) - Boriani, G; Maisano, A; Bonini, N; Albini, A; Imberti, J F; Venturelli, A; Camaioni, G; Passiatore, M; De Mitri, G; Nanni, G; Girolami, D; Siena, V; et al.
Abstract: Background: During the COVID-19 pandemic, implementation of telemedicine has represented a new potential option for outpatient care. Purpose: The aim of our study was to evaluate digital literacy among cardiology outpatients. Methods: From March to June 2020 a survey on telehealth among cardiology outpatients was performed. Digital literacy was investigated through six main domains: age; sex; educational level; Internet access; availability of Internet sources; knowledge and use of teleconference software programs. Results: The study included 1067 patients, median age 79 years, 41.3% females. The majority of the patients (58.0%) had a secondary school degree, but among patients aged ≥75 years old the most represented educational level was primary school or none. Overall, for Internet access, there was a splitting between "never" (42.1%) and "every day" (41.0%), while only 2.7% answered "at least 1/month" and 14.2% "at least 1/week". In the total population, the most used devices for Internet access were smartphones (59.0%), and WhatsApp represented the most used app (57.3%). Internet users were younger compared to non-Internet users (63 versus 78 years old, respectively) and with a higher educational level. Age and educational level were associated with non-use of Internet (age-per 10-year increase odds ratio [OR] 3.07, 95% confidence interval [CI] 2.54–3.71, secondary school OR 0.18, 95% CI 0.12–0.26, university OR 0.05, 95% CI 0.02–0.10) (Figure 1). Conclusions: Telemedicine represents an appealing option to implement medical practice, and for its development it is important to address the gaps in patients' digital skills, with age and educational level being key factors in this setting. FUNDunding Acknowledgement: Type of funding sources: None.